EM-lens enhanced power transfer and multi-node data transmission for implantable medical devices - Feng,P; Maslik,M; Constandinou,T (IEEE, 2019)
This paper presents a robust EM-lens-enhancedwireless power transmission system and a novel multiple-nodedata communication method for distributed implantable medicaldevices. The proposed techniques can solve the common issuescaused by multiple implanted devices, such as low power transferefficiency through biological tissues, uneven delivered powerfor distributed devices and interference between simultaneouswireless power and data transmission. A prototype system hasbeen manufactured with discrete components on FR4 substrateas a proof of concept. The EM-Lens-enhanced inductive linkscan expand the power coverage of transmitting (Tx) coil from9 mm×5 mm to 14 mm×13 mm, and double the recovered DCvoltage from 1.8 V to 3.2 V at 12.5 mm distance. Data commu-nication is achieved by novel low-power back-scattering CDMAscheme. This permits transmission of data from several nodesall operating with the same carrier frequency simultaneouslyreflecting the power carriers to the primary side. In this paper,we demonstrate simultaneous communication between two nodesat 125 kbps with 1.05 mW power consumption.